Effects of Unfractionated and Low Molecular Weight Heparins on Platelet Thromboxane Biosynthesis “In Vivo” - Landolfi, Raffaele; De Candia, Erica; Rocca, Bianca; Ciabattoni, Giovanni; Antinori, Armando; Masetti, Riccardo; Patrono, Carlo (Thrombosis and Haemostasis, 1994)
Several “in vitro” and “in vivo” studies indicate that heparin administration may affect platelet function. In this study we investigated the effects of prophylactic heparin on thromboxane (Tx)A2 biosynthesis “in vivo”, as assessed by the urinary excretion of major enzymatic metabolites 11-dehydro-TxB2 and 2,3-dinor-TxB2. Twenty-four patients who were candidates for cholecystectomy because of uncomplicated lithiasis were randomly assigned to receive placebo, unfractionated heparin, low molecular weight heparin or unfractionaed heparin plus 100 mg aspirin. Measurements of daily excretion of Tx metabolites were performed before and during the treatment. In the groups assigned to placebo and to low molecular weight heparin there was no statistically significant modification of Tx metabolite excretion while patients receiving unfractionated heparin had a significant increase of both metabolites (11-dehydro-TxB2: 3844 ± 1388 vs 2092 ±777, p <0.05; 2,3-dinor-TxB2: 2737 ± 808 vs 1535 ± 771 pg/mg creatinine, p <0.05). In patients randomized to receive low-dose aspirin plus unfractionated heparin the excretion of the two metabolites was largely suppressed thus suggesting that platelets are the primary source of enhanced thromboxane biosynthesis associated with heparin administration. These data indicate that unfractionated heparin causes platelet activation “in vivo” and suggest that the use of low molecular weight heparin may avoid this complication.